Populisme Agama Ditinjau Dari Perspektif Teologi Katolik - Yustinus Yustinus; Robertus Wijanarko; Gregorius Tri Wardoyo (Studia Philosophica et Theologica, 2023)
This study is intended to critically elaborate Catholic Theology on Religious Populism, primarilly as articulated in the Encyclical Fratelli Tutti (On fraternity and social friendship), and its relevance to critically investigate politics of Religious Poapulism in Indonesia. Since the politics of Populism is corraleted with the politic of religious identity, this research then addresses the correlation of those two political phenomena. We utilize literer study as a method in exploring this study. After doing a biblical critical analysis, which in the Christian Theology considered as the biblical theology; we then investigate the Encyclical Fratelli Tutti, which gives an extentive account on Populism. Catholic theology, we are convinced, gives important contributions to the project of religious moderation and offers critical thoughts on religious populism: Religious Populism could endanger the democratic foundations, such as the recognizion of plurality, neglecting the richts of the marginalized and minority, and induces the crisis of humanity itself.